2016
DOI: 10.1371/journal.pone.0165625
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Disability in Rural Bangladesh: Bangladesh Population-Based Diabetes and Eye Study (BPDES)

Abstract: BackgroundTo assess factors associated with disability in a rural district of Bangladesh.MethodsUsing a population-based systematic sampling technique, data were collected from 3104 adults aged ≥ 30 years from the Banshgram union of Narail district. Data collected included an interviewer administered questionnaire to report physical disabilities including impairment that prevents engagement with paid work, visual, hearing, and mobility as well as mental disabilities. Socio-demographic and anthropometric factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 25 publications
4
16
0
1
Order By: Relevance
“…Some studies across the world have reported a higher prevalence of disability among female but these are mostly limited to the elderly age group. 1,8,10,[12][13][14][15][16][17] A few studies have reported a higher prevalence of disability in males but these used census data, considered all age groups or were outside Asia. 11,[18][19] Education A majority of persons with disability were either illiterate (35.1%) or studied till primary school (29.8%) only.…”
Section: Age and Gender Distribution Of Persons With Disabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies across the world have reported a higher prevalence of disability among female but these are mostly limited to the elderly age group. 1,8,10,[12][13][14][15][16][17] A few studies have reported a higher prevalence of disability in males but these used census data, considered all age groups or were outside Asia. 11,[18][19] Education A majority of persons with disability were either illiterate (35.1%) or studied till primary school (29.8%) only.…”
Section: Age and Gender Distribution Of Persons With Disabilitymentioning
confidence: 99%
“…Other studies using rapid assessment of disability toolkit or otherwise, in India or abroad have also reported low level of education attainment in persons with disability. 8,11,13,15,[20][21][22] Marital status…”
Section: Age and Gender Distribution Of Persons With Disabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some assessments have been conducted on the incidence of cataract surgeries in Bangladesh (Gogate et al, 2010;Lindfield et al, 2008), as well as causes of blindness and visual impairment in Bangladeshi adults (Dineen et al, 2003), blindness related to smoking (Bidwell et al, 2005) and the Bangladesh Population-Based Diabetes and Eye Study (Islam et al, 2016). However, while there is data on age-related eye disorders and on the incidence of eye disorders that most commonly affect people in Bangladesh (Wong et al, 2006;Dineen et al, 2003) there have been little assessment of how this relates to hospital-based treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative cost (four cost components including costs due to lack of access to employment; costs due to children with disabilities losing out on school; costs due to adults helping people with disabilities; and costs due to children helping a family member with disabilities) of disability in Bangladesh is approximately US $1.18 billion per year (Ali, 2014). The prevalence of disability is higher among the rural community (Islam, Bhowmik, Islam, Renzaho, & Hiller, 2016). Therefore, in rural areas disability has a devastating effect on the quality of life of the disabled people (Hosain, Atkinson & Underwood, 2002).…”
Section: Introductionmentioning
confidence: 99%